The Predictive Role of Stock Market Return for Real Activity in Thailand - Jiranyakul, Komain (Asian Journal of Empirical Research, 2013)
Stock market return is one of financial variables that contain information to forecast real activity such as industrial production and real GDP growth. However, it is still controversial that stock market return can have a predictive content on real activity. This paper attempts to investigate the ability of stock market return to predict industrial production growth (or real activity) in Thailand, which is an emerging market economy. The standard causality test and the equal forecast evaluation of nested models are employed. For the purpose of forecasting, the data are divided into two periods: the data for the in-sample and the out-of-sample periods. The test of equal forecasting ability is also used. Using monthly data from January 1993 to December 2011, it is found that the model augmented with stock return variable outperforms the benchmark model in the forecast horizon of two months. The results seem to support the notion that stock market return is a predictor of industrial output growth in the short run. Moreover, the standard Granger causality test using the in-sample data also supports this notion. The findings offers a useful insight to investors, financial managers and policymakers on the role of stock market return in forecasting real economic activity. Specifically, a change in stock market return is a signal for revising investment decision by investors and portfolio managers.